Show me the money! Experimental evidence on preferences for cash vs. digital payment - Ambler, Kate; Bakhtiar, M. Mehrab; Bloem, Jeffrey R.; Uddin, Mohammad Riad (International Food Policy Research Institute, 2025)
In places such as rural Bangladesh, cash is the dominant medium for payments despite potential benefits of digital payments. We offer survey respondents an incentive-compatible choice for compensation: 200 Taka cash or randomly varied mobile money amounts (200-400 Taka). Only eight percent chose digital payment at parity and respondents exhibit an average willingness-to-pay of 43 percent of the payment value to receive cash payment. This preference persists across demographics, including among mobile money account holders. Within-household analysis reveals that 77 percent of the effect stems from individual-level rather than household-level factors, highlighting the importance of demand-side barriers on digital payments.